Determination of the Distribution of the Relaxation Times from Dielectric Spectra - Macutkevic, J.; Banys, J.; Matulis, A. (Nonlinear Analysis: Modelling and Control, 2004)
The dielectric susceptibility measurements are usually interpreted in terms of the relaxation times of various dynamical processes. Using the simple examples of the simulated spectra it is shown how the distribution of these relaxation times can be obtained by means of the integral equations solved with the Tikhonov regularization technique, and the criteria for the choice of the regularization parameter is discussed.